Food-Derived High Arginine Peptides Promote Spermatogenesis Recovery in Busulfan Treated Mice - Wenwen Liu; Wenwen Liu; Lingfeng Zhang; Lingfeng Zhang; Anning Gao; Muhammad Babar Khawar; Fengyi Gao; Wei Li; Wei Li (Frontiers in Cell and Developmental Biology, 2021)
Food-derived peptides with high arginine content have important applications in medicine and food industries, but their potential application in the treatment of oligoasthenospermia remains elusive. Here, we report that high-arginine peptides, such as Oyster peptides and Perilla purple peptides were able to promote spermatogenesis recovery in busulfan-treated mice. We found that both Opp and Ppp could increase sperm concentration and motility after busulfan-induced testicular damage in mice. Further research revealed that Opp and Ppp might promote spermatogonia proliferation, which improved blood-testis barrier recovery between Sertoli cells. Taken together, these high-arginine peptides might be used as a medication or therapeutic component of a diet prescription to improve the fertility of some oligoasthenospermia patients.